Plants Speak. Cultural Discourse in Literature and Textbooks in Early School Education (Third Form) - Machowska-Goc, Jolanta (The Motifs of Fauna and Flora in Literature and Culture, 2018)
The paper investigates and compares and contrasts cultural, literary and textbook discourse is early school education. This type of comparative analysis allows a description of contemporary intermental and intercultural readers. The resulting non-linear representation of the world is one of the truth components in the process of language and culture acquisition.